EXISTENCE OF SOLUTIONS FOR THE AGGREGATION EQUATIONS WITH INITIAL DATA IN MORREY SPACES - Suleiman, Marta L. [UNESP]; Precioso, Juliana C. [UNESP]; Prokopczyk, Andrea C. [UNESP] (My University, 2023)
In this work we consider a class of nonlinear viscous transport equations describing aggregation phenomena in biology. We demonstrate the existence of solutions with initial data in Morrey spaces. We analyze the asymptotic stability of solutions persistence at large times.
Keywords: Asymptotic behavior; Chemotaxis; Morrey spaces; Nonlinear viscous transport equations